Genetic Variation in the Histamine Production, Response, and Degradation Pathway Is Associated with Histamine Pharmacodynamic Response in Children with Asthma - Jones, Bridgette L.; Sherwin, Catherine M. T.; Liu, Xiaoxi; Dai, Hongying; Vyhlidal, Carrie A. (Frontiers in Pharmacology, 2017)
Introduction: There is growing knowledge of the wide ranging effects of histamine throughout the body therefore it is important to better understand the effects of this amine in patients with asthma. We aimed to explore the association between histamine pharmacodynamic (PD) response and genetic variation in the histamine pathway in children with asthma. Methods: Histamine Iontophoresis with Laser Doppler Monitoring (HILD) was performed in children with asthma and estimates for area under the effect curve (AUEC), maximal response over baseline (Emax), and time of Emax (Tmax) were calculated using non-compartmental analysis and non-linear mixed-effects model with a linked effect PK/PD model. DNA isolation and genotyping were performed among participants to detect known single nucleotide polymorphisms (SNPs) (n=10) among genes (HDC, HNMT, ABP1, HRH1, HRH4) within the histamine pathway. General linear model was used to identify associations between histamine related genetic variants and measured histamine PD response parameters. Results: Genotyping and HILD response profiles were completed for 163 children. ABP1 47 C/T , ABP1 4107, and HNMT-1639 C/Twere associated with Emax (ABP1 47 CC genotype mean Emax 167.21 vs. CT/TT genotype mean Emax 139.20, p=0.04; ABP1 4107 CC genotype mean Emax 141.72 vs. CG/GG genotype mean Emax 156.09, p= 0.005; HNMT -1639 CC genotype mean Emax 132.62 vs. CT/TT genotype mean Emax 155.3, p=0.02). In a stratified analysis among African American children only, ABP1 and HNMT SNPs were also associated with PD response; HRH4 413 CC genotype was associated with lower Emax, p=0.009. Conclusions: We show for the first time that histamine pathway genetic variation is associated with measureable changes in histamine response in children with asthma. The variability in histamine response and impact of histamine pathway genotype is important to further explore in